2020
DOI: 10.1371/journal.pone.0228446
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of machine learning into clinical breast MRI: Potential for objective and accurate decision-making in suspicious breast masses

Abstract: We investigated whether the integration of machine learning (ML) into MRI interpretation can provide accurate decision rules for the management of suspicious breast masses. A total of 173 consecutive patients with suspicious breast masses upon complementary assessment (BI-RADS IV/V: n = 100/76) received standardized breast MRI prior to histological verification. MRI findings were independently assessed by two observers (R1/R2: 5 years of experience/no experience in breast MRI) using six (semi-)quantitative ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
1
11
0
9
Order By: Relevance
“…To improve the specificity and diagnostic accuracy of MRI findings, researchers have explored the value of multiparametric scoring and evaluation schemes, with varying results [8][9][10][11]. Furthermore, a recent meta-analysis of breast MRI studies concluded that diffusion-weighted imaging with a multiparametric protocol improved the specificity for the diagnosis of malignant lesions but it did not affect the sensitivity [12].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the specificity and diagnostic accuracy of MRI findings, researchers have explored the value of multiparametric scoring and evaluation schemes, with varying results [8][9][10][11]. Furthermore, a recent meta-analysis of breast MRI studies concluded that diffusion-weighted imaging with a multiparametric protocol improved the specificity for the diagnosis of malignant lesions but it did not affect the sensitivity [12].…”
Section: Introductionmentioning
confidence: 99%
“…A large variety of methods belong to the machine learning family, such as artificial neural networks (ANNs), support vector machines (SVMs), but also classic statistical procedures, such as decision trees and regression analysis [46]. Each method provides inherent advantages and has been successfully applied to breast imaging research [14,33,53,54].…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Zur Familie des maschinellen Lernens gehört eine Vielzahl von Methoden wie künstliche neuronale Netze (ANNs), Support Vector Machines (SVMs), aber auch klassische statistische Verfahren wie Entscheidungsbäume und Regressionsanalysen [46]. Jede Methode bietet inhärente Vorteile und wurde bereits erfolgreich in der Brustbildforschung eingesetzt [14,33,53,54].…”
Section: Künstliche Intelligenzunclassified